Spontaneous Propionibacterium Acnes abscess with intraventricular rupture in an immunocompetent adult without prior neurosurgical intervention. Issue 1 (25th January 2022) - Smith, Jordan L.; Cruz‐Gordillo, Peter; Luiselli, Gabrielle; Daci, Rrita; Owusu‐Adjei, Brittany; Ogagan, Charles; Moses, Ziev B.
Abstract: Previously viewed as a culture contaminant, Propionibacterium Acnes can cause infection following neurosurgical intervention. Its role in brain abscess in the immunocompetent, surgically naïve population has been infrequently reported. Herein, we describe an immunocompetent 55‐year‐old man with no risk factors found to have a thalamic abscess with intraventricular rupture. Abstract : Propionibacterium Acnes should be in the infectious differential for all immunocompetent patients presenting with signs of neurologic infection. P .  Acnes should not be automatically considered a contaminant in an immunocompetent patient.